Administrative silence as the challenge in regulation of administrative proceedings. Best practices and successful measures adopted by selected EU countries in the context of Ukrainian law "on administrative procedure" - Йованка Якубек-Лалик (Проблеми Законності, 2023)
The issue of administrative silence is a significant challenge not only for the countries undergoing structural legal reforms, but also in established democracies with stable rule of law systems. Administrative inaction or delayed activity pose serious problems for the citizens, impact their individual rights, but also questions the overall effectiveness of public administration. In general, two models of addressing this case of maladministration are adopted: the negative (where silence means tacit rejection) and positive (where silence means approval). However, in practice of many countries, the solutions are mixed and much more complex. The effective way of dealing with administrative silence seems to be a matter of practice of public administration bodies, good cooperation with administrative courts, and respectful approach to individual rights of the citizens. Ukraine is currently undergoing a major reform of administrative procedure. The newly adopted and currently implemented Law on Administrative Procedure (LAP) provides a comprehensive approach to regulation of administrative proceedings and addresses many challenges relating to the operation of public administration. It is important to test the new solutions and observe how they function in practice, as well as to identify potential weaknesses and possibilities for improvement. Administrative silence, as a substantial challenge to the proper functioning of public administration, needs to be effectively addressed by the legal norms and practice, possibly with the inspiration of the good practices from the other European countries.